Condensation rate effect on top of line corrosion in CO2 environment - Anuar, S.B.S. (Asian Research Publishing Network, 2016)
This research focuses on the effect of condensation rate on top of line corrosion (TLC) for carbon steel (X65) in CO2 environment. The experiment was conducted in a modified glass cell which simulates the TLC phenomena with tested temperature ranging from 25 °C to 55 °C and the cooling temperature was 7 °C. The corrosion rate was measured by the weight loss method and the surface morphology was examined by Scanning Electron Microscopy (SEM) coupled with Energy Dispersive X-ray (EDX). A baseline CO2 corrosion test was also measured simultaneously. The corrosion rate recorded for TLC was in the range from 0.76 mm/year to 1.53 mm/year. Further, the results evident that increase in condensation rate, reduces the corrosion rate which relatively lower than bottom line corrosion rate. The formation of Iron carbonate (FeCO3), which acts as a protective layer is not fully formed and pitting was observed on the surface of the sample. In conclusion, the modified glass cell of TLC experiment was successfully done and it is found that corrosion rate increases with the water condensation rate. ©2006-2016 Asian Research Publishing Network (ARPN).